Design of affinity peptides from natural protein ligands: A study of the cardiac troponin complex. Issue 1 (January 2014) - Chandra, Divya; Sankalia, Nitesh; Arcibal, Imee; Banta, Scott; Cropek, Donald; Karande, Pankaj
ABSTRACT We describe a general strategy for the design and discovery of affinity peptides for a protein from its natural ligands. Our approach is guided by protein–protein interactions in natural systems and focuses on the hetero‐trimeric complex of cardiac troponin I (cTnI), C (cTnC) and T (cTnT). A key premise of this work is that cTnC and cTnT, owing to their innate ability to bind cTnI, are potential templates for the design and discovery of cTnI‐binding peptides. Relying only on the knowledge of primary sequences of cTnC and cTnT, we designed a library of short overlapping peptides that span the entirety of cTnC and cTnT and tested them for binding to cTnI. We were successful in identifying several peptides that display high affinity (1–100 nM) for cTnI. The specific implication of this work is that mimicking natural protein‐protein interactions is an excellent starting point for the discovery and rational design of peptide ligands. The knowledge of secondary or tertiary structures of the proteins involved is not a necessary precondition for this approach. Nevertheless, we show that structural information can be used to validate the results of a fragment‐based peptide design, and can be potentially beneficial for refining the lead candidates. Our approach is broadly applicable to any protein with at least one natural binding ligand with known primary sequence. For protein targets with multiple natural ligands, this approach can potentially yield several distinct affinity peptides capable of simultaneously binding the target protein via orthogonal modes or at complementary interfaces. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 97–106, 2014.